2006
DOI: 10.2115/fiber.62.219
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Higher Order Structures of the Bacterial Polyester Highly Oriented Films

Abstract: IntroductionPoly(3-hydroxybutyrate)(PHB) is produced by a wide variety of microorganisms as intracellular carbon and energy storage material [1], and has been extensively studied as a biodegradable and biocompatible thermoplastic [2][3][4]. However, it is well known that the processing of PHB and its copolymers into fibers, films, and other products is very hard. These polyesters have a glass transition point below room temperature, and the crystallization rate is quite low [5]. Because of these properties, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Irrespective of the roll drawing condition, the highest biaxial draw ratio was achieved at 80 o C. Roll draw ratio also affected the biaxial draw ratio achieved similarly to the results obtained for the uniaxial drawing process. 8 The highest biaxial draw ratio was achieved to the film roll drawn up to ×1.4, although the optimum roll draw ratio for the uniaxial drawing was ×2.0. The films roll drawn up to the ratio higher than ×1.4 tended to break easily in the transverse direction.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Irrespective of the roll drawing condition, the highest biaxial draw ratio was achieved at 80 o C. Roll draw ratio also affected the biaxial draw ratio achieved similarly to the results obtained for the uniaxial drawing process. 8 The highest biaxial draw ratio was achieved to the film roll drawn up to ×1.4, although the optimum roll draw ratio for the uniaxial drawing was ×2.0. The films roll drawn up to the ratio higher than ×1.4 tended to break easily in the transverse direction.…”
Section: Resultsmentioning
confidence: 92%
“…This tendency in the mechanical property has been obtained for the uniaxially drawn PHBH films. 8 In uniaxial drawn PHBH films, the tensile strength and modulus increased monotonically and the elongation at break decreased with increasing uniaxial draw ratio. Crystal deformation and orientation to only MD occurred in the uniaxial drawing process.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…al. [3]. When the extrusion temperature was high, crystallization rate of PHBH was low and molten polymer in the spinning line reached to the take-up bobbin without crystallization, i.e.…”
Section: Appearance Of Prepared Fibersmentioning
confidence: 98%
“…Yamane et al reported that the PHBH fibers can be obtained at the extrusion temperature of 160 °C [3]. They indicated that the crystallization rate was faster if the extrusion temperature was lower than the melting temperature of pure PHB (176°C) and discussed that a certain amount of nucleus was remaining in the polymer melt at this temperature.…”
Section: Introductionmentioning
confidence: 99%